2023
DOI: 10.5194/egusphere-2023-180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of the effects of the Greek extreme wildfires of August 2021 on air quality and spectral solar irradiance

Abstract: Abstract. In August 2021, a historic heatwave was recorded in Greece which resulted in extreme wildfire events that strongly affected the air quality over the city of Athens. Saharan dust was also transferred over Greece in the same period due to the prevailing southern winds. The impact of these events on air quality and surface solar radiation are investigated in this study. Event characterization based on active and passive remote sensing instrumentation has been performed. The study shows that significantl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…It should be noted that the correlation in this study was in a normal condition. In unnormal conditions, such as in the Greek extreme wildfires of August 2021, the UV index at noon decreased by up to 53 % [26]. In this case, their relationship might be shifted.…”
Section: Uv Index Vs Air Temperaturementioning
confidence: 97%
“…It should be noted that the correlation in this study was in a normal condition. In unnormal conditions, such as in the Greek extreme wildfires of August 2021, the UV index at noon decreased by up to 53 % [26]. In this case, their relationship might be shifted.…”
Section: Uv Index Vs Air Temperaturementioning
confidence: 97%
“…For instance, dust episodes from the Sahara Desert are a common natural occurrence, accounting for ~23% of the annually averaged AOD [65]. Other sources are sea-salt aerosols emitted by the surrounding sea bodies [66], biomass burning [67], wildfires [68,69], and photochemical pollution [70,71]. Raptis et al [72] performed a detailed analysis using decadal measurements of aerosol properties (AOD 440 nm and AE 440-870 nm ) from the NOA AERONET station to extract the seasonality and the trends of aerosols in the region.…”
Section: Measurement Sitementioning
confidence: 99%
“…Ιn the histogram in Figure 7, we show the absolute difference between the climatological PWV used in the model and the measured from AERONET It should also be highlighted that for cases of extreme or unpredictable aerosol events, the AOD differences might be a lot higher, thus their propagation to estimated irradiance could be much more significant. During the ASPIRE campaign, there were some days with extreme wildfires in Greece, that were studied by Masoom et al [44], when the decrease of GHI due to smoke was in the range of 10-20%. Another study [45] found that during in a very intense and rare dust event over Athens, the GHI decrease was 40-50% and DNI 80-90%.…”
Section: B Aerosol Effectmentioning
confidence: 99%